Low-pressure synthesis and characterization of multiphase SiC by HWCVD using CH4/SiH4 - Tehrani, F.S.; Badaruddin, M.R.; Rahbari, R.G.; Muhamad, M.R.; Rahman, S.A. (2012)
Silicon carbide (SiC) thin films were deposited by low-pressure hot wire chemical vapor deposition (HWCVD) technique using SiH4 and CH4 gas precursors with no hydrogen dilution. Spectroscopic and structural properties of the films deposited at various methane flow rate (10-100 sccm) and low silane flow rate of 0.5 sccm were investigated. The use of low methane flow rate resulted in a sharp and intense Si-C peak in the Fourier transform infrared (FTIR) absorption spectra. The XRD spectra of the films showed the formation of SiC crystallites at low methane flow rate. The Raman spectroscopy measurements showed the coexistence of a-Si and SiC phases in the films. Increase in methane flow rate increased the carbon incorporation and deposition rate of the SiC films but also promoted the formation of amorphous Si and SiC phases in the films. (C) 2011 Elsevier Ltd. All rights reserved.